PREVALENCE OF PHYSICAL DISABILITY IN SENIOR CITIZENS OF PUNJAB PROVINCE, PAKISTAN - Hamid Mehmood; Abdul Rauf; Muhammad Yaqoob; Saleem Rana (Journal of University Medical & Dental College, 2020)
ABSTRACTBACKGROUND & OBJECTIVE:World Health Organization (WHO) considers that Activities of Daily Living (ADL) is the most important indicator to measure physical and cognitive functions in senior citizens. It is important to know the prevalence of physical disability to find out the needs of senior citizens regarding physical, mental and emotional health. This study has provided us the prevalence rate of physical disability among the senior citizen in the five major cities of Punjab, Pakistan.METHODOLOGY:This descriptive study was conducted over a period of  six months June (06, 2019 to December 05, 2019). The sample was randomly selected. The respondent were senior citizen (Male/Female) having an age of above 60 years. Data were collected from the Index cases. Questionnaire and assessment scales were used as study scale and total sample size was 3675.RESULTS:The results of study showed that the activities of daily living (ADL) and instrumental activities of daily living (IADL) are related to age, sex, education, social and psychological factors. The facilities of education, job, entertainment, social activities vary from city to city. In all cities a p =0.05 was used. In addition, an Eo= 4.5 was set and the reliability to be used was 95%.CONCLUSION:It has been concluded that the physical disability in the senior citizens is increasing due to aging population.